2011
DOI: 10.1103/physrevstper.7.010102
|View full text |Cite
|
Sign up to set email alerts
|

Using multimedia learning modules in a hybrid-online course in electricity and magnetism

Abstract: We have been piloting web-based multimedia learning modules (MLMs), developed by the Physics Education Research Group at the University of Illinois at Urbana Champaign (UIUC), as a ''prelecture assignment'' in several introductory physics courses at California State Polytechnic University at Pomona. In this study, we report the results from a controlled study utilizing modules on electricity and magnetism as a part of a blended hybrid-online course. We asked students in the experimental section to view the MLM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 23 publications
3
42
1
4
Order By: Relevance
“…It should be pointed out that the design of the MLMs used in this study were informed by research in both physics education and multimedia learning. A more in-depth discussion of how the authors of the MLMs utilized the relevant literature in the design process is available in reference [8]. Furthermore, the efficacy of the MLMs has been verified in multiple other settings [5][6][7][8][9].…”
Section: Multimedia Learning Modulesmentioning
confidence: 99%
See 3 more Smart Citations
“…It should be pointed out that the design of the MLMs used in this study were informed by research in both physics education and multimedia learning. A more in-depth discussion of how the authors of the MLMs utilized the relevant literature in the design process is available in reference [8]. Furthermore, the efficacy of the MLMs has been verified in multiple other settings [5][6][7][8][9].…”
Section: Multimedia Learning Modulesmentioning
confidence: 99%
“…For example, improved student learning and attitudes towards instruction have been found when reading assignments have been replaced with on-line multimedia videos in physics classes across various institutions [5][6][7]. In particular, it has been shown that students arrive to class better prepared for learning when completing MLMs versus traditional reading assignments for large-enrollment lecture-based courses and hybrid on-line formats [5,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hace una década, se pudo encontrar en la red (entre vídeos, experimentos interactivos en la pantalla, simulaciones y animaciones generadas por el ordenador) al menos 5000 de multimedia que podrían usarse en la enseñanza de la física (Alther et al 2004). Últimamente, se evalúan experimentalmente sus efectos verdaderos en el aprendizaje de la física de los estudiantes (Sadaghiani 2011, Zacharia y Olympiou 2011, Sadaghiani 2012, Jian-hua 2012, Najafipour et al 2013.…”
Section: El Uso De Vídeo En La Enseñanza Y El Aprendizaje De La Físicaunclassified